Spiritual Exercises for a Secular Age : Desmond and the Quest for God - Duns, Ryan G., 1979- (Book collections on Project MUSE., 2020)
"In A Secular Age, Charles Taylor, faced with contemporary challenges to belief in God, issues a call for "new and unprecedented itineraries" that might be capable of leading seekers to encounter God. In Spiritual Exercises for a Secular Age, Ryan G. Duns demonstrates that William Desmond's philosophy has the resources to offer a compelling response to Taylor. To show how, Duns makes use of the work of Pierre Hadot. In Hadot's view, the point of philosophy is "not to inform but to form"--That is, not to provide abstract answers to abstruse questions but rather to form the human being such that she can approach reality as such in a new way. Drawing on Hadot, Duns frames Desmond's metaphysical thought as a form of spiritual exercise. So framed, Duns argues, Desmond's metaphysics attunes its readers to perceive disclosure of the divine in the everyday. In this way, Desmond's metaphysics is not about conjuring a different reality but instead leads readers to behold reality itself in a different way by helping them to encounter the presence of God, who abides in, and is disclosed through, all things in the world. Spiritual Exercises for a Secular Age offers a readable and engaging introduction to the thought of Charles Taylor and William Desmond, and demonstrates how practicing metaphysics can be understood as a form of spiritual exercise that renews in its practitioners attentiveness to God in all things"-- Back cover.